Asuransi Kesehatan Dalam Hukum Ekonomi : Berdasarkan Perspektif Ilmuan Islam - Abdullah Ali Hamzah; Iin Suryaningsih (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
Health Insurance is a part of insurance that specifically guarantees the health or care costs of insurance members if they fall ill or have an accident. The purpose of this health insurance is to provide health insurance to health insurance recipients, namely entrepreneurs and workers. Such research This can evaluate the economic benefits of health insurance, protection against medical costs, as well as the potential for reducing financial stress when facing health conditions that require expensive treatment. This research was carried out by reading and doing various things, especially studying various literature - existing literature, obtained through qualitative descriptive methods, sourced from books, journals, the internet and articles. The results of this research show that in the Islamic economic view, health insurance is permitted because there is no text that prohibits it and it fulfills the contract or agreement and in it there are elements that are mutually beneficial to both.